RASULULLAH SAW. DAN PRINSIP-PRINSIP KONSELING ISLAM - Lahmuddin Lubis (State Islamic University North Sumatra, 2008)
Abstract: The Prophet and the Principles of Islamic Counseling. From a professional perspective Islamic counseling is a recent origin and few scholars have addressed this area of study in a significant way. This article attempts to highlight the salient features of the principles of Islamic counseling by exploring the Qur’an, the sîrah of the Prophet Muhammad and his traditions as the role model and exemplar, and then compare it to the popular mainstream of western counseling paradigms as a dominant force in counseling and social intervention. The author asserts that psychology, as the origin of western popular counseling, is devoid of religion and foster distorted concepts of humankind that are rooted in materialism whereas counseling that is based on Islam emphasizes spiritual solutions, the main objective of which is to acquire happiness both in this world and the hereafter. Kata Kunci: Rasulullah, konselor, bimbingan, konseling